Peak to Average Power Ratio Reduction in OFDM Using Pulse Shaping Technique - Diptadeep Das (Universitas Sriwijaya, 2016)
Orthogonal Frequency Division Multiplexing (OFDM) is a special type of multicarrier modulation in which a signal is split into several narrowband channels at different frequencies. Here data is divided into parallel data streams each transmitted on a separate band. One of the major drawbacks of multicarrier transmission is the high peak-to-average power ratio (PAPR) of the transmit signal. Nyquist filters provide ISI-free transmission. In this paper we are going to propose some new filters which can formulated in an effort to reduce the peak-to-average power ratio (PAPR) of the baseband signal. While maintaining the same excess bandwidth and the zero inter-symbol interference condition. The proposed filters contain various parameters which gives an additional degree of freedom to minimize PAPR for a given roll-off factor Î± .